THE EFFECT OF WORKİNG HOURS ON LABOR PRODUCTIVITY: DYNAMIC PANEL DATA ANALYSIS - Hakan ACET (Fırat University, 2019)
Today, it is expected that the technological developments will reduce the working hours and allow more leisure time for people. However, the thought that this will negatively affect the economic output is an obstacle to the realization of this expectation. For this reason, the relationship between working hours and per capita output across countries should be examined. In this study, which was conducted to investigate whether the annual working hours affect the output per employee, in other words the labor productivity, except factors such as capital stock, human capital and technology level, a dynamic panel analysis was made using the annual data of 61 countries from 1950 to 2014. According to the estimation results, there is a non-linear relationship between the annual working hours and the labor productivity of the country. While labor productivity increases as working hours increase up to a certain level, increases above this level affect labor productivity in the negative direction. This shows that it is possible and necessary to reduce working hours through legal regulations in countries where working hours are high enough to reduce labor productivity.